LANGUAGE CRIMES AGAINTS IN PRESIDENTIAL CANDIDATE SOCIAL MEDIA X CAPTIONS (FORENSIC LINGUISTIC STUDY) - Pramudya, Dwiki Ayu; R, Dian Karina; Suher, Suher (JURNAL KONFIKS, 2024)
Language crimes are increasingly massive on various social media, carried out intentionally or unintentionally by users as a form of expressive expression. Forensic linguistics is the applied science of linguistics which includes theories, methods and analysis of language in legal issues such as criminal law, civil law, constitutional law, customs and other laws. The aim of this research is to reveal the meaning by describing the types of language crimes from netizens' uploaded captions. on social media X. Forensic linguistics is included in macrolinguistics which combines linguistics and law. Interdisciplinary in this theory is to solve legal problems whose object can be seen from the use of language. The method used is descriptive qualitative with data analysis based on pragmatics and discourse analysis. The object used is the captions uploaded by netizens on social media The diction used is the words be careful, be careful, and don't incite other people. The captions are derogatory with sarcastic expressions and even use harsh words such as kadrun, gedabrus, and ongkang-ongkong. The diction used is total failure, broken, bungul, dummy, KW, and stupid in the insult category. Defamation is described as spreading fake news because account users do not include existing facts. Meanwhile, in the category of hate speech, it is described by the use of harsh diction such as stupid bullshit, hypocritical bangke, sarcastic, bullshit, backbiting, and cheating.